EFFICACY OF GARLIC EXTRACT±ASHWAGANDHA FOR THE TREATMENT OF INFECTIOUS REPEAT BREEDING IN CATTLE - LAWANGE, S R; MARKANDEYA, N M; KUMAWAT, B L; SAWALE, A G; ANBHULE, R S; KADAM, P D (The Indian Journal of Animal Reproduction, 2022)
The present research work was conducted to evaluate the efficacy of Garlic extract intrauterine (IU) versusGarlic extract (IU) plus Ashwagandha powder (oral) for the treatment of fresh (repeated ≤7 times) and chronic(repeated >7 times) infectious repeat breeding in cattle, respectively. Uterine infection was diagnosed by pHestimation, PMN cell count and White Side Test of cervico-vaginal mucus in both fresh and chronic cases whileImmunoglobulin flocculation test with serum in chronic cases only. This indicated 92.8% cows having alkaline pH,PMN cell count >7% and 100% positive for White Side Test and increased immunoglobulin level in blood. Total36 cows affected with endometritis were divided into three groups to undertake treatment on day of estrus viz.Group-I consisting of 12 fresh cases were treated with Garlic extract @10 μg in 30 ml PBS by intrauterine routeonce; Group-II consisting of 12 chronic cases were treated with Garlic extract as per Group-I plus Ashwagandhapowder @ 15 gm with concentrates per oral for 5 days; and Group-III consisting of 12 cows as control were treatedwith placebo @ 30 ml PBS intrauterine. The clinical recovery of cows was confirmed by normal pH, negative whitesite test and PMN cell count
Keywords: Ashwagandha; Cows; Garlic extract; Infectious; Repeat breeder